Genomic characterization of noroviruses from an outbreak associated with oysters - Annika Flint; Jennifer Harlow; Madison McLeod; Madeleine Blondin-Brosseau; Kelly Weedmark; Neda Nasheri (Microbiology Spectrum)
ABSTRACT Human noroviruses are the leading cause of non-bacterial shellfish-associated gastroenteritis. In 2022, a multi-jurisdictional norovirus outbreak associated with contaminated oysters occurred that involved hundreds of illnesses. Here, we conducted genetic analysis on 30 clinical samples associated with this oyster outbreak. We first determined the capsid genotypes by Sanger sequencing and viral titers by droplet-digital reverse transcription PCR. Multiple genotypes were identified in this outbreak, which could indicate contamination with wastewaters. The majority of samples belonged to GII.3[P12], followed by GII.2[P16], GII.17[P17], and GII.4 Sydney[P16]. We next proceeded with whole-genome sequencing and obtained full genomes for 19 samples. Phylogenetic analysis revealed that some of the isolates showed high similarity with the sequences isolated from the United States related to the same outbreak. We also analyzed amino acid variations in the sequenced genomes and found that overall the GII.3[P12] isolates have lower variations compared to other genotypes.IMPORTANCENorovirus outbreaks associated with contaminated shellfish occur frequently. Whole-genome sequencing (WGS) could play a critical role in understanding and controlling norovirus outbreaks as it allows for source attribution, tracking transmission pathways, and detecting recurrent or linked outbreaks. Here, we described how the data obtained by WGS were employed for understanding transmission patterns and norovirus epidemiology.